Probing AGN inner structure with X-ray obscured type 1 AGN. Issue 4 (5th July 2018) - Liu（刘腾）, Teng; Merloni, Andrea; Wang（王俊贤）, Jun-Xian; Tozzi, Paolo; Shen, Yue; Brusa, Marcella; Salvato, Mara; Nandra, Kirpal; Comparat, Johan; Liu, Zhu; Ponti, Gabriele; Coffey, Damien
ABSTRACT: Using the X-ray-selected active galactic nuclei (AGN) from the XMM -XXL north survey and the Sloan Digital Sky Survey-Baryon Oscillation Spectroscopic Survey spectroscopic follow-up of them, we compare the properties of X-ray unobscured and obscured broad-line AGN (BLAGN1 and BLAGN2; N H below and above 10 21.5  cm −2 ), including their X-ray luminosity L X, black hole mass, Eddington ratio λEdd, optical continuum, and line features. We find that BLAGN2 have systematically larger broad line widths and hence apparently higher (lower) M BH (λEdd ) than BLAGN1. We also find that the X-ray obscuration in BLAGN tends to coincide with optical dust extinction, which is optically thinner than that in narrow-line AGN (NLAGN) and likely partial covering to the broad-line region. All the results can be explained in the framework of a multicomponent, clumpy torus model by interpreting BLAGN2 as an intermediate type between BLAGN1 and NLAGN in terms of an intermediate inclination angle.